Warrior diplomat a green beret's battles from Washington to Afghanistan - Waltz, Michael G. (Potomac Books, 2014)
Grappling with centuries-old feuds, defeating a shrewd insurgency, and navigating the sometimes paralyzing bureaucracy of the U.S. military are issues that prompt sleepless nights for both policy makers in Washington and soldiers at war, albeit for different reasons. Few, however, have dealt with these issues in the White House situation room and on the front line. Michael G. Waltz has done just that, working as a policy advisor to Vice President Richard B. Cheney and also serving in the mountains of Afghanistan as a Green Beret, directly implementing strategy in the field that he helped devise in Washington. In Warrior Diplomat: A Green Beret's Battles from Washington to Afghanistan Waltz shares his unique firsthand experiences, revealing the sights, sounds, emotions, and complexities involved in the war in Afghanistan. Waltz also highlights the policy issues that have plagued the war effort throughout the past decade, from the drug trade, to civilian casualties, to a lack of resources in comparison to Iraq, to the overall coalition strategy. At the same time, he points out that stabilizing Afghanistan and the region remains crucial to national security and that a long-term commitment along the lines of South Korea or Germany is imperative if America is to remain secure.